Novel variants and clinical symptoms in four new ALG3-CDG patients, review of the literature, and identification of AAGRP-ALG3 as a novel ALG3 variant with alanine and glycine-rich N-terminus - Himmelreich, Nastassja; Dimitrov, Bianca; Geiger, Virginia; Zielonka, Matthias; Hutter, Anna-Marlen; Beedgen, Lars; Hüllen, Andreas; Breuer, Maximilian; Peters, Verena; Thiemann, Kai Christian; Hoffmann, Georg F.; Sinning, Irmgard; et al. (Human mutation, 2019)
ALG3-CDG is one of the very rare types of congenital disorder of glycosylation (CDG) caused by variants in the ER-mannosyltransferase ALG3. Here, we summarize the clinical, biochemical, and genetic data of four new ALG3-CDG patients, who were identified by a type I pattern of serum transferrin and the accumulation of Man5GlcNAc2-PP-dolichol in LLO analysis. Additional clinical symptoms observed in our patients comprise sensorineural hearing loss, right-descending aorta, obstructive cardiomyopathy, macroglossia, and muscular hypertonia. We add four new biochemically confirmed variants to the list of ALG3-CDG inducing variants: c.350G>C (p.R117P), c.1263G>A (p.W421*), c.1037A>G (p.N346S), and the intron variant c.296+4A>G. Furthermore, in Patient 1 an additional open-reading frame of 141 bp (AAGRP) in the coding region of ALG3 was identified. Additionally, we show that control cells synthesize, to a minor degree, a hybrid protein composed of the polypeptide AAGRP and ALG3 (AAGRP-ALG3), while in Patient 1 expression of this hybrid protein is significantly increased due to the homozygous variant c.160_196del (g.165C>T). By reviewing the literature and combining our findings with previously published data, we further expand the knowledge of this rare glycosylation defect.